Toxic Effect of Blood Feeding in Male Mosquitoes - Nikbakhtzadeh, Mahmood R.; Buss, Garrison K.; Leal, Walter S. (Frontiers in Physiology, 2016)
Blood- and sugar feeding of female mosquitoes has been frequently observed in the laboratory and in the field, but only sugar feeding of males has been reported. Here, we describe for the first time that Culex quinquefasciatus males feed on blood as well. Blood feeding easily happened on a blood-soaked cotton roll and, to a lesser extent, through a thin artificial layer. Mating history of a male specimen does not affect his blood feeding behavior. Male mosquitoes feed on blood even when they have a readily available sugar source. Nevertheless, feeding on blood reduces the survival rate of males to just a few days, as compared to more than a month for mosquitoes fed only on sugar. Comparing survival of male mosquitoes fed on blood only, sugar only, and a combination of both clearly demonstrated that mortality is not affected by malnutrition (reduced sugar levels), but rather due to ingested blood. On average male mosquitoes ingested ca. 0.5 µl of blood, i.e., about 10% of the amount of blood ingested by an engorged female. Although this unexpected observation of blood feeding in the laboratory by male mosquitoes is interesting, structural impairment prevents male feeding on vertebrate blood. In agreement with the literature, male and female proboscises and stylets were in general of similar size, but male mandibles were significantly shorter than female counterparts, thus explaining their inability to pierce through skin layers.